2020
DOI: 10.1111/tme.12674
|View full text |Cite
|
Sign up to set email alerts
|

A single‐centre review of iatrogenic anaemia in adult intensive care

Abstract: Objectives (a) To quantify the volume of diagnostic blood loss (DBL) and evaluate its impact on intensive care unit (ICU) patients, (b) examine the correlation between severity of disease and DBL and (c) identify potentially vulnerable patient subgroups. Background Iatrogenic anaemia is an important problem amongst ICU patients, with significant daily DBL. Methods A single‐centre observational cohort study was conducted at St George's Hospital, London, cardiac and general ICU. Forty patients were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…The volume of blood typically needed for BGA is approximately 2 mL, for serum chemistries it is 7.5 mL, for citrate tubes it is 4.3 mL, for EDTA it is 2.7 mL, and it is up to 6 × 10-20 mL for blood cultures. A systematic review by Siegal et al pointed out that only 10% of collected 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of blood typically needed for BGA is approximately 2 mL, for serum chemistries it is 7.5 mL, for citrate tubes it is 4.3 mL, for EDTA it is 2.7 mL, and it is up to 6 × 10-20 mL for blood cultures. A systematic review by Siegal et al pointed out that only 10% of collected 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also revealed an independent correlation between the increased use of phlebotomy and the risk to develop hospital acquired anemia [29]. 3: General ICU [1,9,10,46,49,50,60]; Medical ICU [27,29,47,48,51,54]; Medical/surgical ICU [11,56,57,62]; Surgical ICU [33,64]; other ICU [32,52,53,55,59,61,63,65].…”
Section: Observational Trialsmentioning
confidence: 95%
See 1 more Smart Citation
“…São inúmeros os pacientes que se beneficiam da transfusão sanguínea, sendo com maior frequência de acordo com a literatura especializada os oncológicos, portadores de afecções hemorrágicas agudas, vítimas de trauma, Coagulação Intravascular Disseminada (CIVD), Púrpura Trombocitopenia Trombótica (PTT), tromocitopênicos e neutropênicos (Cabedal, 2019). Estima-se que paciente internados em Unidade de Terapia Intensiva (UTI) apesentem perda sanguínea de 86,3 ml em quatro dias resultando em anemia dilucional de origem iatrogênica que pode ser percebida com o confronto das variáveis do balanço hídrico e queda de hemoglobina em sete dias de internação (Holland, Peralta, Moss, Feane, & Uprichard, 2020;Witosz, Wojnarowicz, & Krzych, 2021).…”
Section: Introductionunclassified
“…Proposed harms to the patient from excessive laboratory blood testing include injury during phlebotomy, anemia from repetitive phlebotomy, increased central catheter-access potentially leading to central catheter–associated bloodstream infections (CLABSIs), and unnecessary subsequent evaluations for out of range values ( 2 ). An observational study reported that patients were phlebotomized on average 86.3 mL of blood over the course of their first 4 days in the ICU and that nearly half of these patients then required a blood transfusion for anemia ( 3 ). Excessive laboratory utilization can also result in interpretative error and data overload for the physician ( 2 ).…”
mentioning
confidence: 99%